Professional Photography - Scott, Grant (Routledge, 2014)
Since the 2006 photographic digital revolution, the world of professional photography has been on a rollercoaster of evolution. Not only has new camera technology transformed every aspect of the professional photographer's workflow, but it has also changed business practices across the industry. This essential handbook uses a global approach to teach photographers how to thrive in a fast-changing and competitive international marketplace. Highlights include practical examples and detailed advice about: Being well-versed in creating both still and moving images. Designing and maintaining a well-structured website. The importance of engaging with social media. Exploring personal projects to find new clients. Managing print sales and exhibiting. Understanding budgeting and copyright in a digital world. The accompanying podcast interviews with some of today's top professional photographers provide additional insider information to help photographers understand their place in both the commercial and creative worlds.